1994
DOI: 10.1039/ft9949001507
|View full text |Cite
|
Sign up to set email alerts
|

Host–guest complexes of cucurbituril with the 4-methylbenzylammonium lon, alkali-metal cations and NH4+

Abstract: Kinetic measurements indicate the existence of two different complexes of cucurbituril with 4-methylbenzylammonium ions: (i) an association complex, where the ammonium group binds to one of the polar portals of cucurbituril and the hydrophobic part extends into the solvent, and (ii) an inclusion complex, where the hydrophobic part extends into the cavity of cucurbituril. This complex is used as an indicator for the binding of simple monovalent cations to cucurbituril. Stability constants are reported for the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
150
0
7

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(164 citation statements)
references
References 10 publications
7
150
0
7
Order By: Relevance
“…13 Kinetic measurements indicated that 4-methylbenzylammonium produces with CB6 not only inclusion but also exclusion complexes. 14 In the latter, the ammonium group interacts with one of the polar portals of the host and the aromatic moiety extends into the solvent. The equilibrium for the inclusion of protonated cyclohexylmethylamine in CB6 was reached only after several days, whereas the rates of ingression and egression were much faster for the unprotonated amine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Kinetic measurements indicated that 4-methylbenzylammonium produces with CB6 not only inclusion but also exclusion complexes. 14 In the latter, the ammonium group interacts with one of the polar portals of the host and the aromatic moiety extends into the solvent. The equilibrium for the inclusion of protonated cyclohexylmethylamine in CB6 was reached only after several days, whereas the rates of ingression and egression were much faster for the unprotonated amine.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Yu and coworkers found that the dissociation of neutral guests occurs in one step from CB7, but ammonium cyclohexyl derivatives egress in multi-step processes. 29 The hydrophobic, ion-dipole and hydrogen bonding interactions are the strongest in different guest positions in CB7.…”
mentioning
confidence: 99%
“…Desta forma, os cucurbitandos são capazes de formar compostos de inclusão, complexos e adutos com uma enorme variedade de espécies quí-micas 35,36 . Podemos citar entre elas as aminas 12,14,34,[37][38][39] , compostos aromáticos 40,41 , heterocíclicos [42][43][44] , viologênios [44][45][46][47][48][49] , poliaminas, peptídios e aminoácidos [50][51][52] , álcoóis 50,53,54 , surfatantes 53,55 , tióis, gases como CO 2 , O 2 , Kr, N 2 e Xe 31,32,56-58 , metais, complexos e muitas outras, como corantes 59,60 e fármacos [59][60][61][62] (Tabela 2). Em termos de constantes de formação médias de caviplexos de CB [6] com um grande número de compostos, como álcoóis por exemplo, são geralmente uma ordem de grandeza superiores às obtidas com α-ciclodextrinas, mostrando que também exibem uma grande afinidade por moléculas neutras, além de maior seletividade por conta dos fatores mencionados anteriormente.…”
Section: Compostos De Inclusão Com Cucurbitandosunclassified
“…S-shaped oligomers II-5 and II-6 yield CB [5] and CB [6] Behrend's report and disclosed the remarkable macrocyclic structure comprising six glycoluril units and twelve methylene bridges and dubbed it cucurbituril in recognition of its resemblance to a pumpkin which is a prominent member of the cucurbitaceae family ( Figure 1). 2 We refer to cucurbituril as cucurbit [6]uril and abbreviate this as CB [6] In contrast to the host-guest chemistry of -, -, and -cyclodextrin which has developed steadily over the past century, the supramolecular chemistry of CB [6] only began to develop in the 1980's and 1990's due to the pioneering work of Mock, 3 Buschmann, 4 and Kim. 5,6 Interest in the CB[n] family has increased dramatically in the new millennium following the preparation of four new CB[n] homologues (CB [5], CB [7], CB [8], and CB [10]•CB [5]) by the groups of Kim and Day.…”
Section: List Of Figuresmentioning
confidence: 99%
“…1 Figure 2. Chemical structures of -, -, and -cyclodextrin, 18-crown-6, and a calix [4]arene. 3 Figure 3.…”
Section: List Of Figuresmentioning
confidence: 99%